Establishing Caseness, Institutional Selves and "realistic perspectives" - A German Case Study on the Transition from School to Work - Jan Düker; Thomas Ley (Social Work & Society, 2012)
This case study will focus on the institutional and normative framework of the German transition sector and one of its programmes - namely 'Competence Agencies' - its organisational forms and logics of action and the local context they operate in. Main questions will address their identification of problem groups and constructing 'troubled selves' and what they offer for young people in terms of capabilities for work, education and voice. The case study begins with a short framing of the resources, commodities and social policy agenda of the German transition sector and an illustration of the pedagogical programme (chapter 1). Basic research questions are outlined and the research methods are described (chapter 2). The modelling of the object of research embeds it analytically into the current social policy agenda (chapter 3). Three empirical findings are highlighted: Beginning with the questions of which pedagogical space is constituted and how 'caseness' is established, maintained and transformed, the aspects of identity work and institutional selves within these programmes are pointed out. The handling and negotiation of 'realistic perspectives' is a crucial point within this work and provides a link between an institutional and a subject-oriented level (chapter 4). The three capabilities for work, education and voice are the basis for an analytical review of the case study and the conclusion (chapter 5).